2008
DOI: 10.1021/np070526y
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Drug-like Natural Product Library

Abstract: Addressing drug-like/lead-like properties of biologically active small molecules early in a lead generation program is the current paradigm within the drug discovery community. Lipinski's "rule of five" has become the most commonly used tool to assess the relationship between structures and drug-like properties. Sixty percent of the 126 140 unique compounds in The Dictionary of Natural Products had no violations of Lipinski's "rule of five". We have isolated 814 natural products based on their expected drug-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 35 publications
6
100
0
1
Order By: Relevance
“…The majority (80 %) of NPs possess desirable drug-like properties [45]. In a similar fashion, computer-based analysis revealed that NPs exhibit a remarkable structural diversity of molecular frameworks and scaffolds with desirable drug-like properties rendering them ideal starting points for the design of focused libraries [20].…”
Section: Libraries Of Privileged Scaffoldsmentioning
confidence: 95%
See 1 more Smart Citation
“…The majority (80 %) of NPs possess desirable drug-like properties [45]. In a similar fashion, computer-based analysis revealed that NPs exhibit a remarkable structural diversity of molecular frameworks and scaffolds with desirable drug-like properties rendering them ideal starting points for the design of focused libraries [20].…”
Section: Libraries Of Privileged Scaffoldsmentioning
confidence: 95%
“…Lipinski's ''rule of five'' (Ro5) has been proposed to evaluate the drug-likeness of a chemical compound, based on the physico-chemical properties [33]. About 80 % of NPs have less than two violations of the Ro5 [45]. Overall, NPs are more similar to drugs than compounds obtained from combinatorial synthesis [16].…”
Section: Two Sources Of Chemical Spacementioning
confidence: 99%
“…However, recent comparison studies showed that while natural products do differ from drugs in a number of properties and occupy different regions of chemical space, over 60 percent of those registered in the Dictionary of Natural Products do not violate Ro5 properties [69]. Selected natural-product-derived cores have increasingly been considered as attractive scaffolds for the design of natural products like screening libraries [70]. The role of natural products in modern drug discovery is discussed in Chapter 7.…”
Section: Ligand-based Approachesmentioning
confidence: 99%
“…Most of these libraries are focused toward a single target, fully exploiting the high resolution of biostructural information [78], although there are also reports of the same principles of SBDD being applied to the design of target family focused libraries [70]. Several approaches are generally employed to leverage biostructural information for library design.…”
Section: Screening Collection Enhancement Strategiesmentioning
confidence: 99%
“…[2] This was achieved by analyzing all known compounds that comply with Lipinski’s “rule of five” in the Dictionary of Natural Products, and then targeting species known to contain those metabolites. This study was successful in producing a library in which 85 % of the isolated compounds were Lipinski-compliant and therefore drug-like, however the library was biased towards reported compounds, and contained only a limited number of novel structures (around 1 %).…”
mentioning
confidence: 99%